OPEN GOVERNMENT: CASE IN SOUTH COTABATO, PHILIPPINES - Syed Agung Afandi; Rizki Erdayani; Muslim Afandi (Jurnal Kebijakan Pembangunan Daerah, 2024)
The purpose of this study is to examine open government practices and policies in South Cotabato. In this study, bibliometric analysis, content analysis, and a qualitative approach were all employed. South Cotabato policy documents, Scopus, Web of Science, Semantic Scholar, Crossref, and other sources provide research data. The South Cotabato open government study has a high effect and productivity, as evidenced by the 127 related publications, 683 citations, 13 h-index, and 24 g-index that this research found. This study comprises 668 occurrences, 103 topics 9 clusters, and 2646 total link strengths. The subjects that predominate are infrastructure, public monitoring, public information, public participation, open legislation, public access, public service, and extractive. Public service, service quality, access, public information, communication, interactivity, openness, accountability, monitoring, and assessment are among possible research subjects in the interim. At the moment, South Cotabato is concentrating on promises related to open legislation, public involvement in extractives, infrastructure monitoring by the public, and information availability. South Cotabato might become more open as a result of these promises.